Quantitative study on whole brain volume in patients with obstructive sleep apnea based on synthetic magnetic resonance imaging - Yanpeng Li; Xiaomeng Du; Xiaoyan Lang; Zuojun Geng (BMC Medical Imaging)
Abstract Objective To apply SyMRI to quantify whole brain volume changes in patients with varying degrees of obstructive sleep apnea (OSA). Methods A total of 49 untreated adult patients diagnosed with OSA via polysomnography (PSG) at our hospital were included in this study. Among these patients, 21 were categorized into the mild-to‐moderate OSA group, and 28 into the severe OSA group. Additionally, 31 healthy adults were recruited as the healthy control (HC) group. SyMRI post‐processing software was used to obtain whole brain volume segmentation values. Results In terms of the STOP-BANG questionnaire, the score of the severe OSA group was significantly higher than that of the mild‐to‐moderate OSA group (P < 0.05). Compared with the HC group, the mild‐to‐moderate OSA group and the severe OSA group exhibited a reduction in N3‐stage sleep (both P < 0.05). Post‐hoc multiple comparisons showed that compared with the HC group, the severe OSA group had increased GMV, BPV, and ICV, while the mild‐to‐moderate OSA group showed an increase in CSFV (P < 0.05). Additionally, compared with the HC group, the mild‐to‐moderate OSA group exhibited a decrease and the severe OSA group showed an increase in MYV (P < 0.05). Multiple comparisons of normalized volume fractions revealed that GMF, WMF, CSFF, MYF and BPVF were significantly different between the HC group and OSA groups (all P < 0.05). Conclusion The brain volume parameters generated from SyMRI can quantify the degree of brain injury in patients with OSA. Clinical trial number Not applicable.